Design of High Speed and Low-Power Ring Oscillator Circuit in Recessed Source/Drain SOI Technology. (1st January 2019) - Priya, Anjali; Srivastava, Nilesh Anand; Mishra, Ram Awadh
Abstract : In this paper, switching speed of CMOS inverter and Ring Oscillator is analyzed for the first time using Triple-Metal-Gate (TMG) Recessed-Source/Drain (Re-S/D) SOI MOSFET. Re-S/D SOI MOSFET has the capability to reduce the series resistance of the device due to the extended depth of source and drain into buried oxide layer. So the current drive capability of this device is improved which in turn improves the input/output switching in the inverter and ring oscillator. In this paper, transfer characteristics, delay and frequency is analyzed for inverter as well as for ring oscillator with TMG Re-S/D SOI MOSFET. DC and transient analysis such as transfer characteristics, noise margin, power dissipation, delay, and frequency is done for CMOS inverter and ring oscillator. Also, the Voltage Transfer Characteristic (VTC) has been compared with the available SMG and DMG structures of Re-S/D FD SOI MOSFET for the analysis switching behavior. This DC and transient simulation are performed using 2-dimensional numerical TCAD simulator ATLAS from Silvaco.